2005
DOI: 10.1074/jbc.m504113200
|View full text |Cite
|
Sign up to set email alerts
|

DHHC9 and GCP16 Constitute a Human Protein Fatty Acyltransferase with Specificity for H- and N-Ras

Abstract: Covalent lipid modifications mediate the membrane attachment and biological activity of Ras proteins. All Ras isoforms are farnesylated and carboxyl-methylated at the terminal cysteine; H-Ras and N-Ras are further modified by palmitoylation. Yeast Ras is palmitoylated by the DHHC cysteine-rich domain-containing protein Erf2 in a complex with Erf4. Here we report that H-and N-Ras are palmitoylated by a human protein palmitoyltransferase encoded by the ZDHHC9 and GCP16 genes. DHHC9 is an integral membrane protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
352
0
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(368 citation statements)
references
References 39 publications
11
352
0
5
Order By: Relevance
“…Initial data on the biochemical properties of DHHC-CRD protein pointed to the key function of the DHHC motif in palmitoylation but also showed similar acyl transfer properties as observed for Ykt6 (8, 10). However, more recent studies on DHHC-dependent palmitoylation have demonstrated enzymatic activity with turnover numbers ranging between three per min for Ras (13) and two per h for Vac8 (31). This rate is still very poor for Vac8, suggesting that additional factors like Ykt6 and Sec18 increase efficiency of this reaction in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Initial data on the biochemical properties of DHHC-CRD protein pointed to the key function of the DHHC motif in palmitoylation but also showed similar acyl transfer properties as observed for Ykt6 (8, 10). However, more recent studies on DHHC-dependent palmitoylation have demonstrated enzymatic activity with turnover numbers ranging between three per min for Ras (13) and two per h for Vac8 (31). This rate is still very poor for Vac8, suggesting that additional factors like Ykt6 and Sec18 increase efficiency of this reaction in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…The Golgi-localized Akr1 is responsible for palmitoylation of the casein kinase I (CKI) isoform Yck2 (10). Similarly, several of the 20 or so mammalian DHHC proteins localize to distinct organelles, with critical roles for the palmitoylation of PSD-95, Ras, and SNAP-25 (11)(12)(13). This wide distribution of proteins involved in palmitoylation suggests that palmitoylation is not restricted to one organelle but may occur at multiple sites.…”
mentioning
confidence: 99%
“…Until recently no Erf2 orthologs or other proteins featuring Ras S-palmitoylation activity had been found in the genomes of eukaryotes, including the human genome. However, two proteins or protein complexes (DHHC9 and GCP16) that may be involved in Ras palmitoylation have recently been discovered 61,62 .…”
Section: Palmitoylation Of Prenylated Proteinsmentioning
confidence: 99%
“…In yeast, Erf2/Erf4 complex stimulates palmitoylation of Ras2 (similar to mammalian H-Ras and N-Ras) (Lobo et al 2002). In humans, H-and N-Ras are palmitoylated by a DHHC9/GCP16 complex localized in the Golgi complex (Swarthout et al 2005).…”
Section: Introductionmentioning
confidence: 99%